Splošna podhladitev - Mekjavić, Igor B. (Medicinski razgledi, 2002)
This study was conducted to test a hypothesis that inhalation rewarming provides a thermal increment to central neural structures adjacent to the nasopharyngeal region. Auditory-evoked brainstem responses of 14 subjects (7 males and 7 females) were monitored for 25 minutes while they inhaled room air(24degreesC), followed by hot air (41 degreesC) saturated with water vapor and cold dry air (-1degreeC). The latencies of peaks I, III, and V and the interpeak latenaes (IPLs) I-III, III-V, and I-V were compared among the three conditions with repeated ANOVA measurements. Changes in IPLs are sensitive markers of changes in brain temperature. Tympanic temperature (TL ) was measured using an infrared tympanic thermometer. There were no significant differences in Tty, peak latencies I, III, and V, or IPLs I-III, III-V, and I-V The results indicate that inhalat on of hot and cold air does not influence Tty nor does it influence the temperature of the brainstem. It was concluded that inhalation rewarming is incapable of warming the vital neural structures adjacent to the nasopharynx.
Keywords: hipotermija; podhladitev; ogrevanje; inhalacije